Low Concentration of Ethylene Glycol Improved Recovery Rate of Human Spermatozoa After Vitrification (ETILEN GLIKOL KONSENTRASI RENDAH MENINGKATKAN RECOVERY RATE SPERMATOZOA MANUSIA PASCAVITRIFIKASI) - Widyastuti, Rini; Sumarsono, Sony Heru; Boediono, Arief; Rasad, Siti Darodjah (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
The use of cryoprotectants for the cryopreservation of human spermatozoa, oocytes, zygote, earlycleavage stage of embryos and blastocyst is an integral part of almost every human In Vitro Fertilizationprogram. Moreover, the cryopreservation of these types of cells by direct plunging into liquid nitrogen (-196°C) usually requires a high concentration of cryoprotectant with a consequent of cytotoxic effect. Theaim of this study was to observe the effect of ethylene glycol concentration on the spermatozoa recoveryrate following vitrification process. Earle’s balanced salt solution + 0.25 M sukrosa + 1 % human albumineserum as basic solution supplemented with some different concentrations of etylene glycol (ie: 36.25%;18.25%; 9.12%; 4.56%; 1.14% and 0.57%) were used to evaluate the motility and viability of spermatozoafollowing vitrification. Human’s spermatozoa from ejaculates with progressive motility and viability above50% were used as samples. Samples were mixed with vitrification solution and then loaded into 0.25 mLstraws, equilibrated for 10 minutes at room temperature before plunged into liquid nitrogen. Spermatozoathawing was done at 24 hours after the vitrification. The results showed that, the decrease of spermatozoamotility and viability were observed at the highest (100%, 96.70%, respectively) in the samples that wereadded with vitrification medium contained 36.25% of ethylene glycol. On the other hand, the decrease ofthe spermatozoa motility and viability were found at the lowest (14.11%, 43.81 %, respectively) in thesamples without ethylene glycol supplementation. It can be concluded that the highest spermatozoa recoveryrate was obtained from the vitrification using a low concentration of ethylene glycol.
Keywords: cryoprotectant; vitrification; ethylene glycol; spermatozoa motility; spermatozoa viability